Arsenic Induces GSK3β-Dependent p-Tau, Neuronal Apoptosis, and Cognitive Impairment via an Interdependent Hippocampal ERα and IL-1/IL-1R1 Mechanism in Female Rats. (22nd August 2022) - Gupta, Keerti; Vishwakarma, Jitendra; Garg, Asmita; Pandey, Rukmani; Jain, Veena; Gupta, Raksha; Das, Uttara; Roy, Somendu; Bandyopadhyay, Sanghamitra
Abstract: Arsenic is an environmental contaminant with potential neurotoxicity. We previously reported that arsenic promoted hippocampal neuronal apoptosis, inducing cognitive loss. Here, we correlated it with tau pathology. We observed that environmentally relevant arsenic exposure increased tau phosphorylation and the principal tau kinase, glycogen synthase kinase-3 beta (GSK3β), in the female rat hippocampal neurons. We detected the same in primary hippocampal neurons. Because a regulated estrogen receptor (ER) level and inflammation contributed to normal hippocampal functions, we examined their levels following arsenic exposure. Our ER screening data revealed that arsenic down-regulated hippocampal neuronal ERα. We also detected an up-regulated hippocampal interleukin-1 (IL-1) and its receptor, IL-1R1. Further, co-treating arsenic with the ERα agonist, 4, 4', 4″-(4-Propyl-[1H]-pyrazole-1, 3, 5-triyl)trisphenol (PPT), or IL-1R antagonist (IL-1Ra) resulted in reduced GSK3β and p-tau, indicating involvement of decreased ERα and increased IL-1/IL-1R1 in tau hyperphosphorylation. We then checked whether ERα and IL-1/IL-1R1 had linkage, and detected that although PPT reduced IL-1 and IL-1R1, the IL-1Ra restored ERα, suggesting their arsenic-induced interdependence. We finally correlated this pathway with apoptosis and cognition. We observed that PPT, IL-1Ra and the GSK3β inhibitor, LiCl, reduced hippocampal neuronal cleaved caspase-3 and TUNEL+ve apoptotic count, and decreased the number of errors during learning and increased the saving memory for Y-Maze test and retention performance for Passive avoidance test in arsenic-treated rats. Thus, our study reveals a novel mechanism of arsenic-induced GSK3β-dependent tau pathology via interdependent ERα and IL-1/IL-1R1 signaling. It also envisages the protective role of ERα agonist and IL-1 inhibitor against arsenic-induced neurotoxicity.